Physiological and Functional Roles of Neurotrophin-4 During In Vitro Maturation of Porcine Cumulus–Oocyte Complexes - Kim, Mirae; Hwang, Seon-Ung; Yoon, Junchul David; Lee, Joohyeong; Kim, Eunhye; Cai, Lian; Choi, Hyerin; Oh, Dongjin; Lee, Gabsang; Hyun, Sang-Hwan (Frontiers in Cell and Developmental Biology, 2022)
Neurotrophin-4 (NT-4), a granulosa cell-derived factor and a member of the neurotrophin family, is known to promote follicular development and oocyte maturation in mammals. However, the physiological and functional roles of NT-4 in porcine ovarian development are not yet known. The aim of this study was to investigate the physiological role of NT-4-related signaling in the in vitro maturation (IVM) of porcine cumulus–oocyte complexes (COCs). The NT-4 protein and its receptors were detected in matured porcine COCs via immunofluorescence analysis. NT-4 was shown to promote the maturation of COCs by upregulating NFKB1 transcription via the neurotrophin/p75NTR signaling pathway. Notably, the mRNA expression levels of the oocyte-secreted factors GDF9 and BMP15, sperm–oocyte interaction regulator CD9, and DNA methylase DNMT3A were significantly upregulated in NT-4-treated than in untreated porcine oocytes. Concurrently, there were no significant differences in the levels of total and phosphorylated epidermal growth factor receptor and p38 mitogen-activated protein kinase between NT-4-treated and untreated cumulus cells (CCs); however, the level of phosphorylated ERK1/2 was significantly higher in NT-4-treated CCs. Both total and phosphorylated ERK1/2 levels were significantly higher in NT-4-treated than in untreated oocytes. In addition, NT-4 improved subsequent embryonic development after in vitro fertilization and somatic cell nuclear transfer. Therefore, the physiological and functional roles of NT-4 in porcine ovarian development include the promotion of oocyte maturation, CC expansion, and ERK1/2 phosphorylation in porcine COCs during IVM.